Prospective evaluation of complications associated with orthosis and prosthesis use in canine patients - Rosen, Sydney; Duerr, Felix Michael; Elam, Lindsay Hochman (Frontiers in Veterinary Science, 2022)
Introduction The use of orthoses and prostheses is expanding in veterinary medicine. However, research evaluating the efficacy and complications of these devices in veterinary patients is limited. The primary objective of this study was to prospectively determine the complications and outcomes associated with custom orthosis and prosthesis use in the canine patient. Materials and Methods This was a prospective, clinical trial that followed patients for 12 months following device fitting. Owner-perceived complications, clinical metrology instruments, and objective gait analysis were used as outcome measures at various time points. The patients were grouped into the following four major categories: Patients with a carpal orthosis, patients with a stifle orthosis, patients with a tarsal orthosis, and patients with a prosthetic device. Results Forty-three patients were included in the study. Thirty-nine out of 43 patients (91%) experienced at least one complication, with 7/7 (100%) prosthesis patients experiencing at least one complication. At least one skin complication was reported for the following patient groups during the first 3 months of use: 8/14 (58%) stifle orthoses, 9/10 (90%) carpal orthoses, 6/10 (60%) tarsal orthoses, and 4/7 (58%) prostheses. Patient non-acceptance of the device was identified in 2/15 (14%) stifle orthoses, 1/10 (10%) tarsal orthoses, and 4/7 (55%) prostheses. One out of 15 (7%) stifle orthoses, 4/10 (40%) carpal orthoses, 4/10 (40%) tarsal orthoses, and 1/7 (15%) prostheses experienced mechanical device problems necessitating repair. The majority of patients with carpal and stifle orthoses showed improvement on objective gait analysis in percent body weight distribution of the affected limb between baseline and the most recent follow-up without the device donned: 83% (n = 6) of patients with carpal orthoses, 100% (n = 11) of patients with stifle orthoses. None of the patients with tarsal orthoses showed a similar improvement (0%; n = 4). Discussion and conclusion Three major complications associated with canine orthosis and prosthesis use were identified in this study as follows: Skin complications (abrasions, loss of hair, and sores), mechanical device problems, and patient non-acceptance of the device. Owners should be notified of these potential complications prior to pursuing orthoses or prostheses as a potential treatment option. Although clinical improvement was noted in the majority of patients with stifle and carpal pathology, given the lack of a control group, it is unknown how much of this improvement can be attributed to the orthoses.